Derivation of predicted no-effect concentrations for thirty-five pharmaceuticals and personal care products in freshwater ecosystem - Fan, Hailin; Wang, Yuwen; Liu, Xiaojuan; Wang, Yolina Yu Lin; Kazmi, Syed Shabi Ul Hassan; Ohore, Okugbe Ebiotubo; Liu, Wenhua; Wang, Zhen (Frontiers in Marine Science, 2022)
Pharmaceuticals and personal care products (PPCPs) are contaminants of emerging concern. PPCPs have been detected in various environmental matrices, posing potential threat to human health and environment quality. Thus far, there are no water quality guidelines (WQGs) established for PPCPs for the protection of freshwater organisms and ecosystems. In this study, we used the species sensitivity distribution (SSD) and assessment factor (AF) approaches to derive the 5% hazardous concentrations (HC5) of 35 selected PPCPs using acute and chronic toxicity data. The predicted no-effect concentrations (PNECs) and the acute-to-chronic ratios (ACRs) of chemicals were inherently computed to support the derivation of WQGs and for ecological risk assessment. Among these, endocrine-disrupting chemicals and antipsychotics were shown to pose a greater threat to the freshwater environment and organisms. The highest PNEC was recorded for chloramphenicol (3,620 μg/L) and the lowest for fluoxetine (0.0000291 μg/L), which could have significant ecological risks. In addition, the commonly used default ACRs do not seem to provide adequate support for the prediction of chronic toxicity thresholds and WQGs, as the highest ACRs of these drugs reached 39,100 (e.g., chloramphenicol). The findings of this study provide critical scientific information regarding the development of WQGs for environmental management and the risk control of PPCPs.